HR MANAGEMENT - Kasim S. Biktyakov (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article discusses issues of practical HR management, which are used by liner managers in their everyday work. The author puts forward effective technologies and methods of HR work for practical application. The material provides full and objective idea about problems connected with HR management and methods of their resolving. Special attention is paid to innovative managerial conceptions and settlement of the most  widely-spread situations in HR work.